The Role of Branding in Increasing Revisit at Agritourism in Jatiluwih Bali - I Gusti Ayu Oka Suryawardani; Agung Suryawan Wiranatha; I Ketut Satriawan; Ida Bagus Gde Pujaastawa; Eka Nila Kencana; I Wayan Tika (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
Competitiveness of Bali tourism lays on the variety of attractions offered to visitors. Subak-based agritourism in Jatiluwih is one of the competitiveness of cultural based of Bali tourism which offer an amazing rice field terrace and variety of agritourism activities. Understanding the role of brand destination in influencing satisfaction of visitors is very important. Evaluating relationship between satisfaction and intention to be loyal are crucial. The research objectives were: (i) to analyze the influence of brand awareness, brand image and brand association of Jatiluwih agritourism to perceive quality (satisfaction) of foreign tourists in visiting Jatiluwih, and (ii) to evaluate relationship between satisfaction of foreign tourist to their loyalty. Research was conducted at Jatiluwih of Bali Province in the periods of June up to August 2016. The number of respondents was 207 foreign tourists who were visiting Jatiluwih. Structural Equation Model (SEM) was developed and data was analyzed by using Smart PLS-3 based on the five-point Likert scale. The results show that (i) brand awareness, brand images and brand association of subak-based agritourism in Jatiluwih significantly influenced satisfaction of foreign tourist, (ii) satisfaction of foreign tourist significantly influenced their loyalty, (iii) Awareness to a brand, create images to a brand and can associate a brand before visiting a destination have proved that brand destination of Jatiluwih have been an informational signal for visitors who intent to visit Jatiluwih agritourism in Bali.